Effectiveness of Projek Penguatan Profil Pelajar Pancasila Learning to Strengthening Character Formation in Al Karomah Kindergarten and Bhayangkari Kindergarten Kotabaru - Rusdiamah, Rusdiamah; Wahyu, Wahyu; Noorhapizah, Noorhapizah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to describe and analyze the Effectiveness of Projek Penguatan Profil Pelajar Pancasila Learning to Strengthening Character Formation in Al Karomah Kindergarten and Bhayangkari Kindergarten Kotabaru. This research is a qualitative descriptive study. Data were collected through interviews, observations and documentation and analyzed through single-site data analysis and multi-site data analysis. The results of the study showed: 1) Teachers have good abilities in determining learning strategies and methods; 2) Teachers have good abilities in designing learning materials; 3) Teachers have the ability to choose the right learning media; 4) The ability of teachers to evaluate learning in the formation of student character is categorized as good; 5) The ability of teachers to teach in the formation of student character is categorized as good.